Targeted delivery of interleukin-10 to chronic cardiac allograft rejection using a human antibody specific to the extra domain A of fibronectin. (15th September 2015) - Franz, Marcus; Doll, Fabia; Grün, Katja; Richter, Petra; Köse, Nilay; Ziffels, Barbara; Schubert, Harald; Figulla, Hans R.; Jung, Christian; Gummert, Jan; Renner, André; Neri, Dario; et al.
Abstract: Background and aims: Management of chronic rejection is challenging since there are not sufficient preventive or therapeutic strategies. The rejection process leads to overexpression of ED-A + fibronectin (ED-A + Fn). The human antibody F8, specific to ED-A + Fn, may serve as a vehicle for targeted delivery of bioactive payloads, e.g. interleukin 10 (IL-10). The aim of this study was to investigate the therapeutic effects of the fusion protein F8-interleukin-10 (F8-IL10) in the process of chronic rejection development. Methods: A heterotopic rat heart transplantation model was used to induce chronic rejection. For therapeutic interventions, the immunocytokines F8-humanIL10 (DEKAVIL), F8-ratIL10 as well as KSF-humanIL10 (irrelevant antigen-specificity) were used. Treatment was performed weekly for 10 weeks starting at day 7 after transplantation (1 mg/animal). Results: In the cardiac allografts, treatment with F8-huIL10 or F8-ratIL10 was associated with increased heart weights, a higher grade of chronic rejection, increased CIF, higher protein expression levels of alpha-smooth muscle actin (α-SMA), an augmented infiltration with inflammatory cells (CD4 +, CD8 + and CD68 + cells) and higher serum levels of brain natriuretic peptide (BNP) compared to the control groups. Conclusions: All observed treatment effects are transplantation-specific since the F8 antibody is specific to ED-A + Fn that is not expressed in healthy hearts. A clear targeting effect of F8-huIL10 as well as F8-ratIL10 could be proven. Against that background, a further study is needed to address the question, if F8-IL10 treatment is capable to reduce CAV and CIF starting at a time point when chronic rejection has fully developed (therapeutic approach).